The Acheulean workshop of la Noira (France, 700 ka) in the European technological context. (30th January 2016) - Moncel, Marie-Hélène; Despriée, Jackie; Voinchet, Pierre; Courcimault, Gilles; Hardy, Bruce; Bahain, Jean-Jacques; Puaud, Simon; Gallet, Xavier; Falguères, Christophe
Abstract: The prehistoric site of la Noira, located in the Cher Valley, a tributary of the Loire River in the center of France, has yielded a lithic assemblage composed of large bifacial tools, cores and flakes. The archaeological level, lying on the Tertiary lacustrine limestone bedrock, was covered and fossilized by a 6 m-thick fluvial sandy formation. The mean age value of ESR dates obtained on bleached fluvial quartz grains sampled in the sandy levels covering the archeological level is 665 ± 55 ka, confirming the antiquity of the archaeological assemblage. ESR dates and the technical characteristics of the assemblage suggest that it is among the oldest sites with bifacial technology in Western Europe. Since 2011, following geological and geochronological studies, the archaeological level has been excavated over a surface of about 100 m 2. The aim of this paper is to provide new data on the lithic assemblage and to place the lithic patterns of the site in the European technological framework. La Noira is a workshop site, belonging to a key-period of time with the earliest evidence of the bifacial technology in Europe (as for instance levels P–Q of Arago in France or Notarchirico in Italy) contemporaneous with 800–500 ka sites without bifacial technology, such as Happisburgh, Pakefield in England or Isernia in Italy. This phase predates the wide-scale dissemination of the bifacial technology all over Western Europe from the MIS 12. Technological comparisons between these assemblages and a discussion of the diversity of assemblages and technological features point to early episodic arrivals of new traditions in Europe against a background of earlier traditions.